The native cultures through "Raíces" : A video game as a didactic-cognitive resource - Fava, Laura Andrea (2017)
The inclusion of Information Communication Technologies (ICT) in education is something that has been working from different initiatives worldwide. Concern is on how these resources can enhance the teaching-learning process. Video games are an alternative, given that they present an opportunity to work on different themes in a motivating way. Children and young people can access the different contents by critically analyzing the information presented and acting accordingly. The video game Raíces is an innovative tool in social sciences, offering a ludic environment, making the learning process more attractive and motivating than with traditional methods. This article describes the experience of using Raíces in the primary school classroom. We hope that Raíces will help to spread knowledge and to become aware of the problems of native people, seeking to strengthen the conception of Argentina as a multiethnic country.